Biodiversity and Antimicrobial Potential of Acidophilic and Acidotolerant Actinomycetes - A. V. Chumak; O. N. Sineva (Антибиотики и Химиотерапия)
The spread of antibiotic resistance in pathogenic microorganisms is one of the main problems of modern medicine. Given the unique metabolic properties of extremophilic microorganisms, the search for producers of new antimicrobial compounds among extremophilic actinomycetes is reasonably justified. The review examines acidophilic and acidotolerant actinomycetes, which are an integral part of the microbiomes of acidic soils and, as studies show, have high antimicrobial potential.